2016
DOI: 10.1080/1389224x.2016.1207550
|View full text |Cite
|
Sign up to set email alerts
|

What influences transfer of training in an African agricultural research network?

Abstract: What influences transfer of training in an African agricultural research network? The International Center for Tropical Agriculture (CIAT) believes that open access contributes to its mission of reducing hunger and poverty, and improving human nutrition in the tropics through research aimed at increasing the eco-efficiency of agriculture. CIAT is committed to creating and sharing knowledge and information openly and globally. We do this through collaborative research as well as through the open sharing of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Despite the inconsistent findings on peer and supervisor support in the HRD literature, this study provides empirical evidence that strengthens the value of peers in higher education. Applying new KSA is not an isolated behavior but the outcome of complex relationships between supervisor support, peer support and the extent to which this complexity can encourage managers’ dedication and persistence to learn as well as to transfer leadership KSA (Muthoni & Miiro, 2017; Shafloot, 2012). Engaging academic managers and their peers and superiors in designing the training may yield better outcomes especially with the increasing pressure on university professors to compete, publish and perform multi‐tasks with limited resources available to them.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the inconsistent findings on peer and supervisor support in the HRD literature, this study provides empirical evidence that strengthens the value of peers in higher education. Applying new KSA is not an isolated behavior but the outcome of complex relationships between supervisor support, peer support and the extent to which this complexity can encourage managers’ dedication and persistence to learn as well as to transfer leadership KSA (Muthoni & Miiro, 2017; Shafloot, 2012). Engaging academic managers and their peers and superiors in designing the training may yield better outcomes especially with the increasing pressure on university professors to compete, publish and perform multi‐tasks with limited resources available to them.…”
Section: Discussionmentioning
confidence: 99%
“…(2018), Zamani et al . (2016), Muthoni and Miiro (2016), Ataei and Zamani (2018), and Miiro et al . (2012, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…There are only a few transfer studies in agriculture, leaving many areas of agriculture unresearched. Specific studies focusing on agricultural training transfer include: Sseguya et al (2018), Zamani et al (2016), Muthoni and Miiro (2016), Ataei and Zamani (2018), and Miiro et al (2012Miiro et al ( , 2014. All these studies looked at the transfer of training levels among farmers and all showed transfer differences between men and women.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations